Measurement of Serum Anti-staphylococcal Antibodies Increases Positive Predictive Value of Preoperative Aspiration for Hip Prosthetic Joint Infection. Issue 12 (December 2020) - Bauer, Thomas; Marmor, Simon; Ghout, Idir; Salomon, Elsa; El Sayed, Faten; Heym, Beate; Ropers, Jacques; Rottman, Martin; Gaillard, Jean-Louis; Roux, Anne-Laure
Abstract: Background: Preoperative synovial fluid culture is pivotal in the early diagnosis of prosthetic joint infection (PJI) but may yield false-positive and false-negative results. We evaluated the predictive value of synovial fluid culture results combined with the measurement of serum anti-staphylococcal antibodies (SASA). Questions/purposes: (1) For hip and knee PJI, does combining positive SASA results with preoperative synovial culture results improve the positive predictive value (PPV) of preoperative synovial fluid culture alone? (2) Does combining preoperative synovial fluid culture results with a positive cell count and differential result increase the PPV of preoperative synovial fluid culture alone? (3) What proportion of isolated organisms exhibit concordance in antibiotic susceptibility: preoperative aspiration versus intraoperative isolates? Methods: A prospective study was conducted at two French reference centers that manage bone and joint infections and included 481 adult patients who had a revision or resection arthroplasty between June 25, 2012 and June 23, 2014. Exclusion criteria including no serum sample available for immunoassay, the lack of microbiological documentation, and the absence of preoperative aspiration reduced the patient number to 353. Seven patients with an undetermined SASA result were excluded from the analysis. We also excluded patients with PJI involving more than one Staphylococcus species (polystaphylococcal infection) and those in whom more than one Staphylococcus species was recovered from the preoperative synovial fluid culture (polystaphylococcal synovial fluid culture). In total, 340 patients were included in the analysis (no infection, 67% [226 of 340]; staphylococcal infection, 21% [71 of 340]; other infection, 13% [43 of 340]). The preoperative synovial fluid analysis included a cell count and differential and bacterial culture. SASAs were measured using a multiplex immunoassay. The diagnosis of PJI was determined using the Infectious Diseases Society of America (IDSA) criteria [14 ] and intraoperative tissue culture at the time of revision surgery was used as the gold standard (at least one positive intraoperative sample for a "virulent" organism (such as S. aureus ) or two positive samples for a "non-virulent" (for example S. epidermidis ). Results: SASA increased the PPV compared with synovial fluid culture alone (92% [95% CI 82 to 97] versus 79% [95% CI 68 to 87]; p = 0.04); when stratified by site, an increase in PPV was seen in hip infections (100% [95% CI 89 to 100] versus 77% [95% CI 63 to 88]; p = 0.01) but not in knee infections (84% [95% CI 66 to 95] versus 80% [95% CI 64 to 91]; p = 0.75). A positive cell count and differential result increased the PPV of staphylococcal synovial fluid cultures compared with synovial fluid culture alone (86% [95% CI 70 to 95] versus 79% [95% CI 68 to 87]; p = 0.36); when stratified by site, no difference in hip and knee infections was observed (86% [95% CI 67 to 96] versus 77% [95% CI 63 to 88]; p = 0.42) and 86% [95% CI 70 to 95] versus 80% [95% CI 64 to 91]; p = 0.74). Conclusion: SASA measurement improves the predictive value of synovial fluid cultures of the hip for all staphylococcal organisms, including coagulase-negative staphylococci, but the PPV of SASA plus synovial fluid culture it is not superior to the PPV of synovial fluid cell count/differential plus synovial culture for the knee. Level of Evidence: Level III, diagnostic study.